Web-based Attendance System with Face Recognition - Hong, Yee Zhen; Nordin, Noradila (Multidisciplinary Applied Research and Innovation, 2023)
Attendance marking is one of the methods used to monitor students’ presence in lectures. Attendance is a critical aspect of a student's ability to succeed in a course. It is one of the ways to monitor their presence to ensure their participation in the lectures and class activities to enhance their academic achievement and reduce the frequency of absences without justifiable excuses. Typically, the conventional method used is through manual attendance marking on a piece of paper. This approach has been demonstrated to be forgery-prone, imprecise, and time-consuming as it primarily depends on the human factor. Thus, this paper proposes a web-based attendance system with facial recognition (WAS-FR). WAS-FR uses a live camera face detection feed to display the student details and the current approximated location of the student in each of the student’s enrolled courses. It was found that 56.7% strongly agree that WAS-FR has more advantages than the normal attendance system and 66.7% think that the system is more effective and convenient in taking attendance. The system enables effective attendance marking through its functions to ensure that the students are present and located at the location that they are supposed to be, ready for the lectures, especially when lectures are being conducted online.